2014
DOI: 10.1262/jrd.2013-082
|View full text |Cite
|
Sign up to set email alerts
|

Prematurational Culture with 3-Isobutyl-1-methylxanthine Synchronizes Meiotic Progression of the Germinal Vesicle Stage and Improves Nuclear Maturation and Embryonic Development in <i>In Vitro</i>-grown Bovine Oocytes

Abstract: The objective of this study was to clarify the effects of prematurational culture (pre-IVM) supplemented with 3-isobutyl-1-methylxanthine (IBMX) on nuclear and cytoplasmic maturation of in vitro-grown bovine oocytes. In experiment 1, oocytes (95 μm in diameter) derived from early antral follicles (0.5–1 mm in diameter) were cultured for 12 days for in vitro growth (IVG). IVG oocytes with a normal appearance were subjected to examinations of diameter and chromatin structure in the germinal vesicle (GV) before I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, the detailed mechanisms involved in this process require further investigation. Because manipulating the kinetics of meiosis during IVM is important to improve subsequent fertilisation and embryonic development, many inhibitors such as hypoxanthine and IBMX are used to promote oocyte cytolasmic maturation in vitro (Eppig and Downs 1987;Hegele-Hartung et al 1999;Herrick 2014;Huang et al 2014). However, there is an inverse relationship between the duration of oocyte culture and degeneration (Sirard and First 1988;Ali and Sirard 2002): a long duration of IVM leads to oocyte degradation (Alm et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed mechanisms involved in this process require further investigation. Because manipulating the kinetics of meiosis during IVM is important to improve subsequent fertilisation and embryonic development, many inhibitors such as hypoxanthine and IBMX are used to promote oocyte cytolasmic maturation in vitro (Eppig and Downs 1987;Hegele-Hartung et al 1999;Herrick 2014;Huang et al 2014). However, there is an inverse relationship between the duration of oocyte culture and degeneration (Sirard and First 1988;Ali and Sirard 2002): a long duration of IVM leads to oocyte degradation (Alm et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Theophylline also increases the concentration of cAMP in the cytoplasm of sperm by inhibiting phosphodiesterase (PDE) and stimulates sperm motility [ 14 ]. It has been demonstrated that a stable and high fertilization rate [ 15 ] and a blastocyst developmental rate of about 40% [ 16 , 17 , 18 ] were achieved by adding theophylline to bovine IVF medium at a fixed sperm concentration of 5 × 10 6 cells/ml recovered by a Percoll gradient (45 and 90%) procedure. However, in the case of IVF with a low dose of sperm, such as sex-sorted sperm (2.1 × 10 6 cells/straw) [ 19 ], the number of motile sperm might be insufficient for an IVF protocol using medium supplemented only with theophylline.…”
mentioning
confidence: 99%
“…For the growth, prematuration and maturation of oocytes in vitro, the medium was TCM‐199 supplemented with 4% polyvinylpyrrolidone (PVP), 1 µg/ml estradiol, 4 mM hypoxanthine, 0.2 mM pyruvic acid, 2.2 mg/ml sodium bicarbonate, 5.0 mg/ml luteinizing hormone (LH) (Bioniche, Belleville, ON, Canada), 0.5 mg/ml FSH (Bioniche), 5% fetal bovine serum and 100 IU/ml penicillin and 50 mg/ml streptomycin sulfate. The growth medium composition was according to a protocol described previously by Huang, Nagano, Kang, Yanagawa, and Takahashi (), but with the addition of FSH and LH. The COCs were cultured individually for 48 hr in growth medium alone.…”
Section: Methodsmentioning
confidence: 99%
“…3.2 | Experiment 2: Effects of in vitro culture on the levels of mRNAs for GDF9, CCNB1, H1FOO, cMOS, PARN, and eIF4E in oocytes from secondary follicles fetal bovine serum and 100 IU/ml penicillin and 50 mg/ml strepto-mycin sulfate. The growth medium composition was according to a protocol described previously by Huang, Nagano, Kang, Yanagawa, and Takahashi (2014), but with the addition of FSH and LH. The COCs were cultured individually for 48 hr in growth medium alone.…”
Section: Genesmentioning
confidence: 99%